PENGARUH E-SERVICE QUALITY DAN BRAND IMAGE TERHADAP MINAT BELI BUKALAPAK PADA GENERASI MILENIAL DI INDONESIA - Utami, Fitriani Nur (JURNAL ILMIAH EDUNOMIKA, 2024)
The aim of this research is to determine and analyze the magnitude of the influence of e-service quality and Brand Image on the buying interest of the millennial generation in Indonesia. This research uses quantitative methods with descriptive research type. To collect data, we used a non-probability sampling method, namely purposive sampling and collected it from the responses of 96 people using questionnaires sent via social media platforms including Instagram, Whatsapp and Facebook. With the help of SPSS 27, research was analyzed using descriptive analysis and multiple linear regression analysis on the processed data. The results of descriptive analysis reveal that the variables studied, namely e-service quality, brand image, and purchase interest fall into the good category with respective percentages, namely e-service quality 72.49%, brand image 55%, and purchase interest 53%. The results of the hypothesis test show that the e-service quality and brand image variables have a significant influence on the buying interest of the millennial generation in Indonesia. As much as 83.2% of purchasing interest is influenced by e-service quality and brand image. The rest is influenced by other variables, namely Social Media Marketing, Perceived Trust, E-WOM, customer satisfaction at 16.8%.